2019
DOI: 10.1037/xge0000492
|View full text |Cite
|
Sign up to set email alerts
|

Child homicides by stepfathers: A replication and reassessment of the British evidence.

Abstract: Daly and Wilson report that rates of fatal assaults of young children by stepfathers are over 100 times those by genetic fathers, and they explain the difference in evolutionary terms. Their study was replicated using updated homicide data, and population data from three surveys. The risk to young stepchildren was approximately 16 times that to genetic children, and stepfathers were twice as likely to kill by beating. However, when father's age was controlled for, the risk from cohabiting fathers was approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(67 citation statements)
references
References 31 publications
(162 reference statements)
3
63
1
Order By: Relevance
“…In addition, the abusive stepfathers in this sample were predominantly young men. This finding converges with that of Nobes et al (2019) whose recent analysis of child homicides indicated that many perpetrators were young, casual and short-term partners of their victims' mothers. In fact, in that study, many of the perpetrators hardly knew the children and were therefore likely to have been misclassified as stepfathers.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, the abusive stepfathers in this sample were predominantly young men. This finding converges with that of Nobes et al (2019) whose recent analysis of child homicides indicated that many perpetrators were young, casual and short-term partners of their victims' mothers. In fact, in that study, many of the perpetrators hardly knew the children and were therefore likely to have been misclassified as stepfathers.…”
Section: Discussionsupporting
confidence: 85%
“…Of course, the ecological and evolutionary accounts are not necessarily mutually exclusive, and genetic relatedness might be one of the many factors that explain child abuse by stepparents. However, the findings of this and other recent studies (Nobes et al, 2019;Temrin et al, 2011;Turner et al, 2007) The data from this Colombian sample indicate that the high rates of physical abuse by stepfathers resulted at least partly from numerous factors, perhaps beginning with parents' experience of abuse when they were children, and its subsequent intergenerational transmission via stressors such as interpersonal conflict and unstable relationships. There seems also to be an important role for the genetic mothers in this process.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Second, the risk of infanticide by a stepparent is significantly higher when children are within the 0-5 age range but drops significantly among older children (Daly and Wilson 1988). Finally, children of younger mothers are most at risk of violence (Daly and Wilson 1985;Nobes et al 2019).…”
Section: Introductionmentioning
confidence: 99%